STUDY OF SPORT TALENT IN MALE STUDENTS OF CLASS VII SMP NEGERI 2 JATEN - Muh Arif Dwi Saputro; Sunardi Sunardi; Ahmad Septiandika Adirahma (Universitas Sebelas Maret, 2021)
The purpose of this study was to determine the sporting talent in male students of class VII SMP Negeri 2 Jaten the academic year 2019/2020. This research uses a descriptive method. This study wanted to describe giftedness in male students of class VII SMP Negeri 2 Jaten. The population and sample in this study were male students of class VII SMP Negeri 2 Jaten in the academic year 2019/2020. The subjects in this study were male students of grade VII SMP Negeri 2 Jaten in the academic year 2019/2020 as many as 100 students. Data collection techniques in this study used tests and measurements of the sports search model which consisted of 10 test items, namely: height, sitting height, body weight, length of the two arms, throwing a tennis ball, throwing basketball, jumping upright, running agility. , sprint 40 meters and run multi-stage. The data analysis technique used computer software